Literature Review: An Analysis of the Implementation of Public Service Agency (BLU) Towards Sinta-Indexed Public Sector Accountability - Agneswati Arifin Putri; Zudin, Nanda Nabila; Rizty Nur Afifah; Naura Salsabilah; Lilis Karisma (Jurnal Dialektika: Jurnal Ilmu Sosial, 2024)
This study aims to examine the implementation of public sector accountability in Public Service Agencies (BLU) in Indonesia. The research was conducted from 2016 to 2024 through a review of journals indexed by SINTA. This study uses a literature review approach. Based on the review, this study identified 15 accredited journals on the implementation of BLU indexed by SINTA. Financial management flexibility, including cash management, debt management, investment management, revenue, and expenditure management, is granted to entities applying the Regional Public Service Agency Financial Management Pattern (PPK-BLUD) in accordance with their characteristics. Effective financial management allows the entity to receive and use income directly without first depositing it into the regional treasury. In addition, BLUD entities are authorized to self-manage funds by retaining and using liquid funds for short-term investments. These two factors affect BLUD accounting and financial transactions, which are ultimately represented in the BLUD Financial Statements. Although some agencies still face challenges in optimally implementing BLU principles in financial management and reporting, the study results show that the application of BLU in various public sector institutions has increased the efficiency and flexibility of public services. Keywords: Public Service Agency (BLU), Accountability, Transparency, Reporting, Flexibility